Optimization of fulvic acids production from oil palm empty fruit bunches using microwave extractor - Firda Dimawarnita; Khairy Yunda Maharani; Yora Faramitha; Donny Nugroho Kalbuadi; Haryo Tejo Prakoso; Indah Puspita Sari; Dedy Prasetyo; Sutanto Sutanto; Didiek Hadjar Goenadi (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2024)
Fulvic acid (FA) derives from a non-renewable source, Shilajit, known as highly commercial values for its benefit for human health. Fulvic acid can also be extracted from materials such as coal, lignite, and peat. Extraction methods of FA generally use solid acids and bases, ion exchange chromatography, and their combinations. However, these methods cause corrosion, low purity, and environmental pollution. The FA extraction using organic solvents is common, but low yielded, and many organic solvents are toxic. Therefore, an effective way to separate organic solvents from FA must be determined. This research aims to extract the FA from renewable biomass, namely oil palm empty fruit bunches (OPEFB), using a microwave extractor combined with hydrogen peroxide. The advantage of using a microwave is its quick and efficient extraction process. Hydrogen peroxide is an environmentally friendly solvent that can be converted into water and oxygen. Fulvic acid extraction was optimized using expert design with the Response Surface Methodology method with optimization of four 4 factors (H2O2 concentration and volume, reaction time, and microwave power). The extracted FA was then characterized using FTIR, H-NMR, and Fluorescennce spectroscopy. The highest FA concentration namely 24.716%, was obtained using H2O2 at a concentration of 30.46% with a volume of 137.4139 mL, reaction time of 9.384 minutes, and microwave power of 351.39 W. Fourier-Transform Infrared Spectroscopy peaks at 3213 cm-1, 2935.47 cm-1, and 2825.13 cm-1 in the OPEFB-FA sample indicate existence of FA. The fluorescent emission intensity ratio between 450/500 nm wavelengths of OPEFB-FA was 0.719.